Mucins and polysaccharides from Echinococcus granulosus laminar layer induce a mild maturation phenotype in dendritic cells and promote gene expression of pro-inflammatory cytokines - Plá, Natalia (2020)
Background: The laminar layer is an acellular structure rich in glycans that surrounds the metacestode, creating a mechanical and immunological protective barrier, crucial in the Echinococcus?host interface. The aim of this work is to analyze if purified laminar layer (pLL) could trigger maturation and cytokine production in dendritic cells by activating mTOR pathway, a central regulator of cell metabolism and environmental signals. Methods: BMDCs were cultured in complete RPMI supplemented with 100 ng/ml Flt3-L.The germinal layer was removed from pLL by washing with 2M NaCl. Flow cytometry: FITC or PE-conjugated mAbs directed to CD11c, CD40, CD80, CD86, MHC I and MHC II were used. Immunobloting and confocal microscopy: mouse anti-puromycin and rabbit anti-Phospho-mTOR antibodies were used. Gene expression analysis of IL-10, IL-12p35, IL-6, TNF-, IL-23p19, TGF- was performed on a Real Time PCR System Results: The pLL of Echinococcus induce a non-statistically significant, but a trend in the up-regulation of CD86 and MHC II and that expression change was diminished by the use of rapamycin (n=5). Conversely, no changes in the expression of CD40, CD80 or MHC I were registered. Further studies were done to analyze whether pLL was also able to stimulate the production of cytokines by BMDCs. When BMDCs were stimulated with pLL induce the expression of IL-6 and TNF-an=3 *p<0.05, **p<0.01), but not differences compared to control were observed in IL-12, IL-23, IL-10 and TGF-. Finally, we evaluated global protein synthesis and phosphorylation of mTOR using confocal microscopy or western blot. pLL (MFI:_979) showed an increase in translation levels compared to its counterpart without stimulation (MFI:_686, *p<0.05 n=3) and also induce an increase in mTOR phosphorylation levels compared to untreated BMCDs (n=3, p<0.01) Conclusions: These data suggest that Echinococcus pLL are recognized by DCs and induce activation of mTOR pathway favoring cell activation.